Referee personal meaning: Perception of football officials - Brandão, Regina; Serpa, Sidónio; Krebs, Ruy; Araújo, Duarte; Machado, Alfonso Antonio [UNESP] (My University, 2011)
The aim of this study was to evaluate the personal meaning of refereeing for Portuguese football referees. Participants were 47 football referees from the 1st Portuguese Professional Football League evaluated through an open question: Write down what refereeing means to you. The analysis was made according to Miles and Huberman (1994) procedures. The 5 categories are: relation with the football; costs of the practice; emotion for the arbitration; social interaction and way of life. The results show that be connected to the world of the football, passion and the relationship with other referees are important motivational factors, with that the referees have a high grade of excitement and pleasure in his labor activity. On the other hand the task of refereeing is generating of stress and burnout.
El significado de arbitrar: Percepción de jueces de fútbol profesional
Keywords: Football; Officiating; Perception